Gli antagonisti del recettore GPIIb/IIIa: farmacologia, clinica ed economia nelle sindromi coronariche acute NSTEMI e nelle rivascolarizzazioni per via percutanea - Pradelli, Lorenzo (Farmeconomia. Health economics and therapeutic pathways, 2005)
Inhibition of platelet glycoprotein IIb/IIIa (GP IIb/IIIa) receptor prevents platelet aggregation by controlling its final common pathway, the cross-binding of fibrinogen, bridging across adjacent platelets. Three pharmacological agents capable of inhibiting GP IIb/IIIa are available for use in Italy: abciximab, eptifibatide and tirofiban. In this paper, some relevant studies on the pharmacology of GP IIb/IIIa inhibitors are summarized, as well as the main clinical trials assessing their use in the management of unstable angina (UA) and during percutaneous coronary interventions (PCI). Furthermore, the recommendations on their appropriate use in UA and PCI issued by authoritative scientific societies are presented. Finally, some of the pharmacoeconomic evidence published in the international literature is reviewed and implications in the Italian health care setting are discussed.